Leaf-size control beyond transcription factors: Compensatory mechanisms - Tabeta, Hiromitsu; Gunji, Shizuka; Kawade, Kensuke; Ferjani, Ali (Frontiers in Plant Science, 2023)
Plant leaves display abundant morphological richness yet grow to characteristic sizes and shapes. Beginning with a small number of undifferentiated founder cells, leaves evolve via a complex interplay of regulatory factors that ultimately influence cell proliferation and subsequent post-mitotic cell enlargement. During their development, a sequence of key events that shape leaves is both robustly executed spatiotemporally following a genomic molecular network and flexibly tuned by a variety of environmental stimuli. Decades of work on Arabidopsis thaliana have revisited the compensatory phenomena that might reflect a general and primary size-regulatory mechanism in leaves. This review focuses on key molecular and cellular events behind the organ-wide scale regulation of compensatory mechanisms. Lastly, emerging novel mechanisms of metabolic and hormonal regulation are discussed, based on recent advances in the field that have provided insights into, among other phenomena, leaf-size regulation.